Heat transfer enhancement, intensification and optimisation in heat exchanger network retrofit and operation. (March 2020) - Klemeš, Jiří Jaromír; Wang, Qiu-Wang; Varbanov, Petar Sabev; Zeng, Min; Chin, Hon Huin; Lal, Nathan Sanjay; Li, Nian-Qi; Wang, Bohong; Wang, Xue-Chao; Walmsley, Timothy Gordon
Abstract: The improvement of heat recovery in the industry has traditionally been approached from two different viewpoints – Process Intensification and Process Integration. Many of the developments took the form of Heat Transfer Enhancement or Heat Integration within Heat Exchanger Networks, developing in parallel. In the past decade, however, there have been successful applications of both approaches together, resulting in cost benefits for heat-integrated retrofits. Heat Integration literature has continued to provide a variety of network modelling and retrofit approaches. Recent reviews of the area show that the mathematical-based and thermodynamic-based approaches have reached maturity within the current modelling paradigm. There are indications that the modelling concepts and frameworks need a further step-change to bridge the gap between the solutions to heat recovery problems offered by the current methods and the practical implementation in terms of real retrofit actions, leading to economically feasible reduction of energy use and emissions. The current paper takes these indications as a departure point and reviews the history and the recent developments in the areas of Heat Transfer Enhancement and the retrofit of Heat Exchanger Networks, providing a critical analysis from the viewpoint of obtaining practical solutions with positive cash flows, while minimising the issues related to operability – emissions, flexible operation and control. The analysis clearly shows the need to focus future research and development efforts on increasing model fidelity and practicality, addressing operability issues, and most importantly – development of flexible and efficient tools for communicating optimisation results to industrial practitioners and plant managers who would implement the process retrofit recommendations. Highlights: Combining Heat Transfer Enhancement and Heat Integration is highly beneficial. Mathematical Programming and thermodynamic retrofit approaches have reached maturity. Solutions for improving Waste Heat Utilisation in the industry need to be more practical. Research objectives should refocus on maximising Life Cycle asset performance. There is an ongoing need to extend the software tools to further support for energy retrofit.